2018
DOI: 10.1093/humupd/dmy022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding variation in prevalence estimates of polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: Inclusion of ovarian morphology results in statistically significantly higher pooled prevalence estimates for PCOS. Heterogeneity in prevalence estimates for PCOS reflect the broad clinical spectrum of the condition, lack of standardization of the elements within each set of diagnostic criteria and the use of a range of diagnostic cut-offs, as well as potential differences between study populations. The use of different definitions for anovulation and clinical androgen excess did not appear to contribute to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
119
4
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 68 publications
2
119
4
5
Order By: Relevance
“…PCOS has a significant prevalence worldwide, with reports of up to 20% of women of reproductive age being affected by the condition, which poses a high economic health burden (March et al 2010, Dumesic et al 2015, Bozdag et al 2016, Skiba et al 2018. PCOS women suffer from a wide range of ill-health traits, which include endocrine, reproductive, metabolic and psychological features.…”
Section: Defining Polycystic Ovary Syndrome (Pcos) and Evidence To Sumentioning
confidence: 99%
“…PCOS has a significant prevalence worldwide, with reports of up to 20% of women of reproductive age being affected by the condition, which poses a high economic health burden (March et al 2010, Dumesic et al 2015, Bozdag et al 2016, Skiba et al 2018. PCOS women suffer from a wide range of ill-health traits, which include endocrine, reproductive, metabolic and psychological features.…”
Section: Defining Polycystic Ovary Syndrome (Pcos) and Evidence To Sumentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) has a prevalence ranging from 5 to 20% in women of reproductive age, depending on the population and criteria used for making a definitive diagnosis (1,2). The use of ultrasound may increase PCOS prevalence by two to threefold and adds two more phenotypes (1).…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) has a prevalence ranging from 5 to 20% in women of reproductive age, depending on the population and criteria used for making a definitive diagnosis (1,2). The use of ultrasound may increase PCOS prevalence by two to threefold and adds two more phenotypes (1). As the criteria used for the diagnosis of PCOS may decrease, or even normalize, during the reproductive lifetime, the prevalence of PCOS seems to decrease with age (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6 Depending on the diagnostic criteria used, 7,8 PCOS affects 6% to 18% of women worldwide in their reproductive years. 2,9 In the Middle East, the prevalence of PCOS is equally high and ranges from 5% based on the National Institutes of Health criteria, to 19% based on the Rotterdam consensus criteria. [10][11][12][13] Several studies have reported a link between PCOS and reduced health-related quality of life (HRQoL).…”
Section: Introductionmentioning
confidence: 99%